PEMANFAATAN GAME EDUKASI ONLINE MATEMATIKA DALAM MENINGKATKAN KEMAMPUAN BERHITUNG SISWA - Aura Rifah Nabila; Dewantri Priyono Putri; Pipit Erawati; Arita Marini (Bajang Institute, 2022)
Education is a conscious and planned effort undertaken to increase the potential of human resources in a country. Meaningful education has three core characteristics, namely prosperity, respect for human dignity, and justice. One example of integrated education is education that is able to develop the creativity of teachers and students. This can be implemented in the classroom by raising subject matter based on the use of technology in its application. The use of online games in learning is intended so that students can more easily understand and remember the learning material provided. The purpose of this study was to determine the effect of using online game media in improving students' numeracy skills. This type of research is qualitative using library research methods. data collection techniques by collecting several sources (literary study) and documentation. From the results of the research we conducted, it was found that online educational games had an effect on improving students' numeracy skills because they could increase students' enthusiasm in doing them so that better results were found